Pengaruh Disiplin dan Pelatihan Kerja Terhadap Prestasi Kerja Karyawan PT Bank Rakyat Indonesia Cabang Cikarang - Yuni Astuti Tri Tartiani; Sisca Devia Sinta (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2023)
The purpose of this study was to find out the problems that often occur in Discipline and Job Training on Work Achievement of Employees of PT Bank Rakyat Indonesia Cikarang Branch. The research method used is descriptive quantitative with a total sample of 50 respondents with a questionnaire to employees of PT Bank Rakyat Indonesia Branch. Cikarang Based on the results of the study that the discipline variable has a significant positive effect on work performance. This study succeeded in proving that work discipline and work training have a significant positive effect on job performance. Discipline and work training simultaneously (simultaneously) affect work performance by 75.9 while the rest are influenced by other factors outside of this study.